Audit Committee Effectiveness and Earnings Management Among Publicly Listed Firms in Kenya - Collins Kapkiyai; Josephat Cheboi; Joyce Komen (SEISENSE (PRIVATE) LIMITED, 2020)
Objective: The paper sought to investigate the role of an effective audit committee in controlling earnings management practices. Design / Methodology: A panel data sourced from the audited financial reports of firms listed at the Kenyan Nairobi Securities Exchange for the periods between 2004 and 2017 were analyzed using a panel regression model. Findings: Audit committee effectiveness proved an important monitoring mechanism for earnings management. The independence, Meeting frequency, and financial expertise of the audit committee evidenced a negative and significant effect on earnings management. Practical Implications: Firms need to ensure that their audit committees operate effectively. This is achieved through enhancing their independence, ensuring optimal meeting frequency, and a higher number of members with financial expertise for fewer earnings management. Originality: The paper suggests the ways through which audit committee effectiveness can be enhanced to reduce earnings management amid rampant global financial scandals.